Waktu Pelaksanaan Senam Aerobik terhadap Mean Arterial Pressure (Map) pada Wanita Usia Subur (WUS) dengan Hipertensi - Septiani, Ainishfi Laili; Anwar, M. Choiroel; Santjaka, Aris (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the timing of the best aerobic exercise in reducing mean arterial pressure as an alternative in dealing with hypertension in women of childbearing age. The research method used was quasy experimental with pretest posttest with control group design. Results of the study showed that the average decrease in MAP of the pre and post morning gymnastics group was 110.76 and 96.21 (p = 0.000), afternoon exercise 106.95 and 93.78 (p = 0.000), and the education group 108.07 and 102.42 (p = 0.008). And the results over time showed (p = 0.239) in week 2, (p = 0.032) in week 4 and (p = 0.000) in week 6. It was concluded that aerobic exercise in the morning was more effective in reducing MAP compared to aerobic exercise in the afternoon and the control group in women of childbearing age. Keywords: Mean Arterial Pressure, Aerobic Gymnastics, Women of Childbearing Age